An Effective Blockchain Based Secure Searchable Encryption System - Ali, Aitizaz; Masud, Mehedi; Rehman, Ateeq Ur; Chen, Can; Mehmood; Alzain, Mohammad A.; Ali, Jehad (Intelligent Automation and Soft Computing, 2022)
Security of Patient health records (PHR) is the most important aspect of cryptography over the Internet due to its value and importance preferably in the medical Internet of Things (IoT). Search keywords access mechanism is one of the common approaches which is used to access PHR from database, but it is susceptible to various security vulnerabilities. Although Blockchain-enabled healthcare systems provide security, but it may lead to some loopholes in the existing schemes. However, these methods primarily focused on data storage, and blockchain is used as a database. In this paper, Blockchain as a distributed database is proposed with homomorphic encryption technique to ensure a secure search and keywords-based access to the database. Moreover, the proposed approach provides a secure key revocation mechanism and update various policies accordingly. A secure patient healthcare data access scheme is devised, which integrates blockchain and trust chain to fulfill the efficiency and security issues in the current schemes for sharing both types of digital healthcare data. Our proposed approach provides improved security, efficiency, and transparency with cost effectiveness. We performed our simulations based on the blockchain based tool termed as the Hyperledger fabric and Origionlab for analysis and evaluation. We have compared our proposed results with the benchmark models. Our comparative analysis justify that our proposed framework gives improvement in security and searchable mechanism for healthcare system.
Keywords: Blockchain; Encryption; Energy optimization; Homomorphic encryption; Secure searchable encryption; Security